The last hero : a Discworld fable - Pratchett, Terry (Pratchett, Terry. Discworld series (New York, N.Y.), 2002)
Disgruntled by the complications of modern life, an aged Cohen the Barbarian calls together a group of his elderly friends to join him in a quest to climb Discworld's highest mountain to meet the gods.